Peran watak kewarganegaraan sebagai landasan etika berinternet mahasiswa - Sirrul Auvia; Sawaludin Sawaludin; Jumrawati Jumrawati (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze the role of civic disposition as a foundation for students’ internet ethics among students of the Pancasila and Civic Education Study Program at the University of Mataram, as well as to identify the factors influencing its internalization. This study employs a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation. The research informants consisted of students and lecturers selected using purposive sampling techniques. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. This study also considers ethical issues in the research process. The findings indicate that civic disposition plays a significant role in shaping students’ internet ethics, as reflected in the values of honesty, responsibility, politeness, discipline, and tolerance. Furthermore, the internalization of civic disposition is influenced by environmental factors, education, emotional or self-regulation, and individual awareness. Therefore, strengthening civic disposition is essential in fostering ethical, wise, and responsible digital behavior among students.